Women increasingly identifying as part of a discriminated group - Sandra Bohmann; Matteo Targa (DIW Weekly Report, 2022)
Policymakers have been attempting to combat discrimination at all levels for a long time. However, the measures they take can only be successful if there is general awareness of the discrimination experienced by certain groups or people: Discrimination can only be addressed when people also recognize and acknowledge it is happening. Therefore, it is important to measure the extent to which the population is aware of discrimination. This Weekly Report examines which individuals feel they belong to a discriminated group in 17 European countries from 2008 to 2018. Overall, not even one in ten respondents feels part of a group that is discriminated against. However, the share of those who view their group at risk of discrimination has risen by a quarter in the decade observed. Women in particular have become increasingly more likely to feel part of a discriminated group. Moreover, the experience of multidimensional discrimination doubled between 2008 and 2018. Other data sources show that the general population perceives discrimination to be declining. This is why the perspective of those affected is important.
Keywords: J71; 330; perceived discrimination; multidimensional discrimination; Europ